2016
DOI: 10.1016/j.ijid.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of cell culture-derived and egg-derived trivalent influenza vaccines in 3 to <18-year-old children and adolescents at risk of influenza-related complications

Abstract: TIVc and TIV had acceptable tolerability and similar safety profiles in at-risk children (NCT01998477).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Safety data (pertaining to both QIVc and the TIVc comparators) from these trials were generally consistent with those from numerous clinical studies of TIVc in adults and children [13, 1822, 2933], with the additional strain not altering the safety profile of the QIVc vaccine; no new safety signals were identified [13]. The clinical development program for TIVc found it to have a safety profile comparable to that of an egg-based trivalent influenza virus vaccine [13, 1822, 31, 32, 34]. Post-marketing safety data are available for TIVc, representing millions of adults and children vaccinated in Europe and the USA in the 2016/2017 influenza season, and have confirmed its established safety profile [13]; similarly, an earlier surveillance study in the USA (2013–2015) found no concerning patterns in the adverse events reported in TIVc recipients [35].…”
Section: Reactogenicity and Safetysupporting
confidence: 70%
“…Safety data (pertaining to both QIVc and the TIVc comparators) from these trials were generally consistent with those from numerous clinical studies of TIVc in adults and children [13, 1822, 2933], with the additional strain not altering the safety profile of the QIVc vaccine; no new safety signals were identified [13]. The clinical development program for TIVc found it to have a safety profile comparable to that of an egg-based trivalent influenza virus vaccine [13, 1822, 31, 32, 34]. Post-marketing safety data are available for TIVc, representing millions of adults and children vaccinated in Europe and the USA in the 2016/2017 influenza season, and have confirmed its established safety profile [13]; similarly, an earlier surveillance study in the USA (2013–2015) found no concerning patterns in the adverse events reported in TIVc recipients [35].…”
Section: Reactogenicity and Safetysupporting
confidence: 70%
“…Moreover, we detected a wider range of AEs as signals with egg-based vaccines compared with cell-based vaccines, suggesting that safety profiles among these two subtypes may differ, which is inconsistent with the results of previous studies. Two RCTs demonstrated that cell-based and egg-based TIVs had comparable safety profiles in children and adolescents < 18 years of age 26,27 . We believe that this situation may be due to the following reasons.…”
Section: Signal Detectionmentioning
confidence: 99%
“…Cell-grown IIVs offer an alternative to egg-based vaccines. Cell-grown QIVs or TIVs have good immunogenicity profiles and may have a modest improvement over egg-based vaccines in children and adolescents (164,165) while having similar safety profiles to those of egg-based IIVs in children (166,167). One study found that the recombinant HA-based vaccine outperformed the virion-based IIV in both HA-specific cellular and serological responses in adults (168).…”
Section: Future Perspectivesmentioning
confidence: 99%